2008
DOI: 10.1097/01.nnr.0000313484.18670.ab
|View full text |Cite
|
Sign up to set email alerts
|

The Validity and Reliability of a Spanish Version of the Summary of Diabetes Self-Care Activities Questionnaire

Abstract: The findings for the psychometric properties of the Spanish version of the SDSCA questionnaire suggest that it has conceptual and content equivalency with the original English version and is valid and reliable. However, further testing with larger samples is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
61
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 18 publications
7
61
0
8
Order By: Relevance
“…The SDSCA has been widely validated, with both English and other populations [30], [31], [32]. To produce comparable scores for CHD and diabetes patients we excluded items related to checking feet and blood sugar.…”
Section: Methodsmentioning
confidence: 99%
“…The SDSCA has been widely validated, with both English and other populations [30], [31], [32]. To produce comparable scores for CHD and diabetes patients we excluded items related to checking feet and blood sugar.…”
Section: Methodsmentioning
confidence: 99%
“…The validity of the SDSCA scale is established 36 . Validity and reliability of the Spanish version of the SDSCA have been reported 37 .…”
Section: Methodsmentioning
confidence: 99%
“…A previous study using this scale reported the average interitem correlations between items to be high (M = 0.47; Toobert, Hampson, & Glasgow, 2000). Validity and reliability of the Spanish scale version administered among Hispanic Spanish-speaking participants has been previously reported by other researchers (Cronbach's α = .68; Vincent, McEwen, & Pasvogel, 2008;. Our sample data yielded a Cronbach's alpha of .64, which is comparable to previous results; however, the average of interitem correlations between the scale items was lower than previously reported in the literature (i.e., M = 0.13).…”
Section: Methodsmentioning
confidence: 93%